(untitled) (Acta Scientiarum. Language and Culture, 2018)
Politics of force today is inseparably connected with politics of images. This paper focuses on the representation of the image of Russia in the British political mass media discourse of 2013-2017. Taking into account K. Boulding’s definition of the image of state as a special concept, the paper claims that this concept includes the notion or nuclear, verbalized with the lexeme ‘Russia’ and its substitutes, and different associations, connected with this notion and thus forming: metaphorical, evaluative and ethnocultural associative layers of the concept. Drawing on the scientific works on problems of mass media discourse, image-formation, associations, structure and verbalization of concepts and using the methods of contextual, critical discourse, seme and conceptual metaphor analysis, the paper reveals the range of means for surfacing the nucleus and layers of the concept ‘Russia, used by British journalists. These means demonstrate ideological values of the discourse in question and stereotypes, which it forms in the minds of British people. The paper suggests that the scheme of analysis of the image of state in the political mass media discourse, offered in it, can be applied to the investigation of images of other states as well as to comparative studies.